Overexpression of Lin28a Aggravates Psoriasis-Like Phenotype by Regulating the Proliferation and Differentiation of Keratinocytes [Corrigendum] - Jang S (Dove Medical Press, 2021)
Jang S, Jang S, Kim SY, et al. J Inflamm Res. 2021;14:4299–4312. The authors have advised the author list on page 4299 is incorrect. The correct author list and affiliations are as follows. Soyeon Jang1,* Soyoung Jang1,* Si-Yong Kim1 Jiwon Ko1 Eungyung Kim2 Ji Yeong Park1 Hyejin Hyung1 Jin Hong Lee1 Su-Geun Lim3 Sijun Park3 Junkoo Yi4 Heon-Jin Lee5 Myoung Ok Kim2 Hyun-Shik Lee1 Zae Young Ryoo1 1School of Life Sciences, BK21 FOUR KNU Creative BioResearch Group, Kyungpook National University, Daegu, Korea; 2Department of Animal Science and Biotechnology, Kyungpook National University, Daegu, Korea; 3School of Life Sciences, Kyungpook National University, Daegu, Korea; 4Gyeongsangbukdo Livestock Research Institute, Yeongju, Korea; 5Department of Microbiology and Immunology, School of Dentistry, Kyungpook National University, Daegu, 41940, Korea *These authors contributed equally to this work Read the original article